Preparation and properties of reactive powder concrete by using titanium slag aggregates. (20th February 2020) - Xiaoying, Li; Jun, Li; Zhongyuan, Lu; Li, Hou; Jiakun, Chen
Abstract: In this research, titanium slag (TS) was used as an alternative aggregate to prepare reactive powder concrete (RPC). The mechanical properties, hydration characteristics, and interface structure of the RPC was investigated. The results showed that the porous, low-activity TS aggregate had high water adsorption and proper secondary hydration during moulding and hardening. This accelerated the early-age hydration reaction of RPC and significantly improved the interfacial structure between paste and aggregate. Ca 2+, Mg 2+, and Si 4+ present in TS leached out and generated additional C-S-H around the aggregate during hydration, which filled the gap between paste and aggregate